Inclusion of cGAMP within virus-like particle vaccines enhances their immunogenicity - Chauveau, L; Bridgeman, A; Tan, TK; Beveridge, R; Frost, JN; Rijal, P; Pedroza-Pacheco, I; Partridge, T; Gilbert-Jaramillo, J; Knight, ML; Liu, X; Russell, RA; et al. (Springer, 2021)
Cyclic GMP-AMP (cGAMP) is an immunostimulatory molecule produced by cGAS that activates STING. cGAMP is an adjuvant when administered alongside antigens. cGAMP is also incorporated into enveloped virus particles during budding. Here, we investigate whether inclusion of cGAMP within viral vaccine vectors enhances their immunogenicity. We immunise mice with virus-like particles (VLPs) containing HIV-1 Gag and the vesicular stomatitis virus envelope glycoprotein G (VSV-G). cGAMP loading of VLPs augments CD4 and CD8 T-cell responses. It also increases VLP- and VSV-G-specific antibody titres in a STING-dependent manner and enhances virus neutralisation, accompanied by increased numbers of T follicular helper cells. Vaccination with cGAMP-loaded VLPs containing haemagglutinin induces high titres of influenza A virus neutralising antibodies and confers protection upon virus challenge. This requires cGAMP inclusion within VLPs and is achieved at markedly reduced cGAMP doses. Similarly, cGAMP loading of VLPs containing the SARS-CoV-2 Spike protein enhances Spike-specific antibody titres. cGAMP-loaded VLPs are thus an attractive platform for vaccination.